Computer-aided image analysis for PD-L1 assessment in canine urothelial carcinoma - L.V. Muscatello; B. Bacci; E. Brigandì; C. Tugnoli; G. Avallone; P. Valenti; A. Giuliano; G. D’Annunzio; C. Benazzi; G. Sarli (The Veterinary Journal, 2026)

Phylogenomics of Melastomataceae: rooting out discordance across organellar and nuclear genomes - Monique Romeiro Brito; Léo-Paul M.J. Dagallier; Lucas F. Bacci; Marcelo Reginato; Malu I. Ore-Rengifo; Serena Acha; Marie Claire Veranso-Libalah; Luo Chen; Gudrun Kadereit; Renato Goldenberg; Ying Liu; Renchao Zhou; et al. (Molecular Phylogenetics and Evolution, 2026)

Morphoanatomical adaptations of stems in Bertolonia (Melastomataceae): how individuals of an ombrophilous lineage survive in drier localities - Gessica C. A. Bisewski; Lucas F. Bacci; Erika Amano; André M. Amorim; Renato Goldenberg; Juliana K. Ziemmer (Plant Biosystems, 2026)

Characterization and insecticidal effects of the essential oil and nanoemulsion of Pogostemon cablin on populations of Sitophilus zeamais - Álvaro M.O. Santos; Ana Paula A. Araújo; Péricles B. Alves; Arie Fitzgerald Blank; Eliseu J.G. Pereira; Raul N.C. Guedes; Rogéria S. Nunes; Marcelo C. Picanço; Virginia E. Masiulionis; Leandro Bacci (Crop Protection, 2026)

Environmental anthracosis as a risk factor for canine pulmonary adenocarcinoma - M. Amalia; C. Palmieri; R. Magalhaes; B. Brunetti; B. Bacci; M. Anjomanibenisi (Journal of Comparative Pathology, 2025)

Description of spatial proliferation patterns in canine neoplasms - E. Brigandì; B. Bacci; B. Brunetti; A. Rigillo; P. Roccabianca; G. Bellini; C. Chiappelli; G. Avallone (Journal of Comparative Pathology, 2025)

Multiplex immunohistochemistry and supervised machine learning for immune cells topography in canine PDL1 tested urothelial Carcinoma - L. Muscatello; T. Franceschini; C. Tugnoli; A. Grillini; B. Bacci; G. Avallone; P. Valenti; M. Fiorentino; G. Sarli (Journal of Comparative Pathology, 2025)

ELIME-IMS hybrid assay for Salmonella detection in swine mesenteric lymph nodes at slaughterhouse - M. Trevisani; M. Conter; M. Cecchini; L. Lamperti; L. Andriani; M. Rega; C. Bacci; M. Perri; S. Bonardi (Food Microbiology, 2025)

Alternative hosts can affect the development, reproduction, and demographic parameters of Chrysodeixis includens - Ane C. C. Santos; Ana Paula A. Araújo; Jaciele O. Dantas; Jefferson E. Silva; Aline M. Pinheiro; Valfran S. Andrade; Natielli C. Santos; Swamy R. S. A. Tavares; Arie F. Blank; Leandro Bacci (Arthropod-Plant Interactions, 2023)

Detection of carbapenemase- and ESBL-producing Klebsiella pneumoniae from bovine bulk milk and comparison with clinical human isolates in Italy - S. Bonardi; C.S. Cabassi; E. Fiaccadori; S. Cavirani; A. Parisi; C. Bacci; L. Lamperti; M. Rega; M. Conter; F. Marra; C. Crippa; L. Gambi; et al. (International Journal of Food Microbiology, 2023)

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest - Andrea Paz; Jason L. Brown; Carlos L. O. Cordeiro; Julian Aguirre‐Santoro; Claydson Assis; Renata Cecilia Amaro; Fabio Raposo do Amaral; Thuane Bochorny; Lucas F. Bacci; Mayara K. Caddah; Fernando d’Horta; Miriam Kaehler; et al. (Journal of Biogeography, 2021)
Aim There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism. Location Brazilian Atlantic Forest. Taxon: Five clades of plants (Bromelioideae, Miconieae, Bertolonia , Cambessedesieae, and the Fridericia and allies) and four clades of animals (butterlies in the tribe Ithomiini, frogs in the genera Boana and Proceratophrys , and birds in the subfamily Thraupinae). Methods Using curated occurrence localities and phylogenetic data, we generated maps of (a) species richness, (b) phylogenetic diversity, (c) residuals of phylogenetic diversity regressed on species richness, and (d) phylogenetic endemism for all groups. We also compiled a set of 30 environmental descriptors, including records of current temperature and precipitation, climatic stability over time, and topography. Through a machine learning framework, we explored the environmental correlates of each of these diversity measures for each group. Results The environmental variables used here were strong predictors of diversity for all studied groups. However, models for phylogenetic endemism had lower predictive power. Although patterns of diversity are different among groups, correlates of diversity are consistent across taxa. For both species richness and phylogenetic diversity, current precipitation and precipitation stability over time were consistently ranked among the variables that strongly correlate with diversity patterns. The correlates of phylogenetic endemism were less homogeneous across groups. The results suggest that including climate stability over time is important when predicting diversity measures that reflect historical components. Main conclusions Investigating environmental correlates of diversity for multiple clades and diversity measures in a single geographic area allows for a better understanding of common patterns across taxa. This study shows that environmental conditions, particularly precipitation, are good predictors of the patterns of species richness and phylogenetic diversity‐but not phylogenetic endemism‐across different Atlantic Forest groups.

Novelties in Bertolonia (Melastomataceae) from northeastern Brazil - Gessica C. A. Bisewski; Lucas F. Bacci; André M. Amorim; Renato Goldenberg (Brazilian Journal of Botany, 2020)

Synergistic effect of aromatic plant essential oils on the ant Acromyrmex balzani (Hymenoptera: Formicidae) and antifungal activity on its symbiotic fungus Leucoagaricus gongylophorus (Agaricales: Agaricaceae) - Carlisson R. Melo; Bruna Maria S. Oliveira; Ane Caroline C. Santos; Jefferson E. Silva; Genésio T. Ribeiro; Arie F. Blank; Ana Paula A. Araújo; Leandro Bacci (Environmental Science and Pollution Research, 2020)

Insecticidal activity of indole derivatives against Plutella xylostella and selectivity to four non-target organisms - Ângela C. F. Costa; Sócrates C. H. Cavalcanti; Alisson S. Santana; Ana P. S. Lima; Thaysnara B. Brito; Rafael R. B. Oliveira; Nathália A. Macêdo; Paulo F. Cristaldo; Ana Paula A. Araújo; Leandro Bacci (Ecotoxicology, 2019)

Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region - C. Rabeling; S. Messer; S. Lacau; I. C. do Nascimento; M. Bacci; J. H. C. Delabie (Insectes Sociaux, 2019)

Acute Toxicity and Sub-lethal Effects of the Essential Oil of Aristolochia trilobata and Its Major Constituents on Nasutitermes corniger (Termitidae: Nasutitermitinae) - A A Santos; C R Melo; B M S Oliveira; A S Santana; A C C Santos; T S Sampaio; A F Blank; P F Cristaldo; A P A Araújo; L Bacci (Neotropical Entomology, 2019)

Pyrene degradation by marine-derived ascomycete: process optimization, toxicity, and metabolic analyses - Maria R. S. Vasconcelos; Gabriela A. L. Vieira; Igor V. R. Otero; Rafaella C. Bonugli-Santos; Marili V. N. Rodrigues; Vera L. G. Rehder; Milene Ferro; Sinésio Boaventura; Maurício Bacci; Lara D. Sette (Environmental Science and Pollution Research, 2019)

Essential oils from Varronia curassavica (Cordiaceae) accessions and their compounds (E)-caryophyllene and α-humulene as an alternative to control Dorymyrmex thoracius (Formicidae: Dolichoderinae) - Bruna M. S. de Oliveira; Carlisson R. Melo; Ane C. C. Santos; Luis F. A. Nascimento; Daniela A. C. Nízio; Paulo F. Cristaldo; Arie F. Blank; Leandro Bacci (Environmental Science and Pollution Research, 2019)

Lethal Effect and Behavioral Responses of Leaf-Cutting Ants to Essential Oil of Pogostemon cablin (Lamiaceae) and Its Nanoformulation - A G Rocha; B M S Oliveira; C R Melo; T S Sampaio; A F Blank; A D Lima; R S Nunes; A P A Araújo; P F Cristaldo; L Bacci (Neotropical Entomology, 2018)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Relative abundance of heat shock proteins and clusterin transcripts in spermatozoa collected from boar routinely utilised in an artificial insemination centre: preliminary results - A. Zannoni; C. Bernardini; A. Zaniboni; E. Ferlizza; D. Ventrella; M. L. Bacci; M. Forni (Veterinary Research Communications, 2017)

Biology of the relict fungus-farming ant Apterostigma megacephala Lattke, including descriptions of the male, gyne, and larva - J. Sosa-Calvo; A. Ješovnik; C. T. Lopes; A. Rodrigues; C. Rabeling; M. Bacci; H. L. Vasconcelos; T. R. Schultz (Insectes Sociaux, 2017)

Life table determination of thermal requirements of the tomato borer Tuta absoluta - J. C. Martins; M. C. Picanço; L. Bacci; R. N. C. Guedes; P. A. Santana; D. O. Ferreira; M. Chediak (Journal of Pest Science, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Long-term efficacy of microbiology-driven periodontal laser-assisted therapy - F. S. Martelli; E. Fanti; C. Rosati; M. Martelli; G. Bacci; M. L. Martelli; E. Medico (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants - C. Rabeling; T. R. Schultz; M. Bacci; M. Bollazzi (Insectes Sociaux, 2015)

Improvement of biomolecular methods for the identification and typing of Escherichia coli O157:H7 isolated from raw meat - A. Paris; S. Bonardi; C. Bacci; E. Boni; F. Salmi; L. Bassi; F. Brindani (Veterinary Research Communications, 2010)

Pulmonary kinetic expression of the endothelin system in a swine model of endotoxic shock - A. Zannoni; C. Bernardini; F. Gentilini; M. Giunti; M. L. Bacci; M. Forni (Veterinary Research Communications, 2010)

Antagonistic interactions between garden yeasts and microfungal garden pathogens of leaf-cutting ants - Andre Rodrigues; Rachel N. Cable; Ulrich G. Mueller; Maurício Bacci; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2009)

First results on the detection of Listeria monocytogenes in raw milk: comparison of two different analytical methods - A. Paris; E. Riboldi; F. Salmi; C. Bacci; S. Bonardi; F. Brindani (Veterinary Research Communications, 2009)

Yeasts and filamentous fungi carried by the gynes of leaf-cutting ants - Fernando C. Pagnocca; André Rodrigues; Nilson S. Nagamoto; Maurício Bacci (Antonie van Leeuwenhoek, 2008)

Detection and count of Salmonella enterica in pork and poultry meat products - S. Bonardi; F. Salmi; E. Riboldi; C. Bacci; F. Brindani (Veterinary Research Communications, 2008)

Molecular phylogeny and karyotype differentiation in Paratelmatobius and Scythrophrys (Anura, Leptodactylidae) - L. B. Lourenço; M. Bacci-Júnior; V. G. Martins; S. M. Recco-Pimentel; C. F. B. Haddad (Genetica, 2008)

Matrix Metalloproteinases -2 and -9 in Swine Luteal Tissue Angiogenesis and Angioregression - L. A. Ribeiro; M. E. Turba; C. Bernardini; A. Zannoni; M. L. Bacci; M. Forni (Veterinary Research Communications, 2007)

Detection and Characterization of Yersinia enterocolitica from Pigs and Cattle - S. Bonardi; A. Paris; C. Bacci; M. D’Incau; L. Ferroni; F. Brindani (Veterinary Research Communications, 2007)

Presence of marRAB Operon in Salmonella spp. Strains Isolated from Pork and Poultry Meat - F. Brindani; C. Bacci; A. Paris; A. Salsi; S. Bonardi (Veterinary Research Communications, 2006)

Susceptibility of the ant-cultivated fungus Leucoagaricus gongylophorus (Agaricales: Basidiomycota) towards microfungi - A. Silva; A. Rodrigues; M. Bacci; F. C. Pagnocca; O. C. Bueno (Mycopathologia, 2006)

Production of Polysaccharidases in Different Carbon Sources by Leucoagaricus gongylophorus Möller (Singer), the Symbiotic Fungus of the Leaf-Cutting Ant Atta sexdens Linnaeus - Aline Silva; Maurício Bacci; Fernando C. Pagnocca; Odair C. Bueno; Maria J. A. Hebling (Current Microbiology, 2006)

Variability of non-mutualistic filamentous fungi associated withAtta sexdens rubropilosa nests - A. Rodrigues; F. C. Pagnocca; M. Bacci; M. J. A. Hebling; O. C. Bueno; L. H. Pfenning (Folia Microbiologica, 2005)

Use of Immunomagnetic Separation Technique and Polymerase Chain Reaction for Detection of Verocytotoxin-Producing Escherichia coli in Cattle at Slaughter - S. Bonardi; C. Bacci; G. Pizzin; B. Orlandini; E. Donati; F. Brindani; E. Foni; C. Chiapponi; E. Aibino (Veterinary Research Communications, 2005)

Nesting biology of the fungus growing ants Mycetarotes Emery (Attini, Formicidae) - S. E. Solomon; U. G. Mueller; T. R. Schultz; C. R. Currie; S. L. Price; A. C. Oliveira da Silva-Pinhati; M. Bacci; H. L. Vasconcelos (Insectes Sociaux, 2004)

Alteration of Constitutive Heat Shock Protein 70 (HSC70) Production by in vitro Culture of Porcine Preimplanted Embryos - C. Bernardini; P. Fantinati; G. Castellani; M. Forni; A. Zannoni; E. Seren; M.L. Bacci (Veterinary Research Communications, 2003)

Occurrence of killer yeasts in leaf-cutting ant nests - S. C. Carreiro; F. C. Pagnocca; M. Bacci; O. C. Bueno; M. J. A. Hebling; W. J. Middelhoven (Folia Microbiologica, 2002)

Relationships between atmospheric circulation patterns and co2 greenhouse-gas concentration levels in the alpine troposphere - A. Longhetto; S. Ferrarese; C. Cassardo; C. Giraud; F. Apadula; P. Bacci; P. Bonelli; A. Marzorati (Advances in Atmospheric Sciences, 1997)

Seasonal and spatial distribution of bacterial production and biomass along a salinity gradient (Northern Adriatic Sea) - A. Puddu; R. La Ferla; A. Allegra; C. Bacci; M. Lopez; F. Oliva; C. Pierotti (Hydrobiologia, 1997)

Location of the β-galactosidase of the yeast Kluyveromyces marxianus var. marxianus ATCC 10022 - M. Bacci Júnior; C. G. Siqueira; S. A. Antoniazi; J. Ueta (Antonie van Leeuwenhoek, 1996)

Cellulose degradation byLeucocoprinus gongylophorus, the fungus cultured by the leaf-cutting antAtta sexdens rubropilosa - M. Bacci; M. M. Anversa; F. C. Pagnocca (Antonie van Leeuwenhoek, 1995)